Phosphorus‐Containing Polymeric Zwitterion: A Pioneering Bioresponsive Probe for 31P‐Magnetic Resonance Imaging - Kracíková, Lucie; Ziółkowska, Natalia; Androvič, Ladislav; Klimánková, Iveta; Červený, David; Vít, Martin; Pompach, Petr; Konefał, Rafał; Janoušková, Olga; Hrubý, Martin; Jirák, Daniel; Laga, Richard (Macromolecular bioscience, 2022)
31P‐magnetic resonance (MR) is an important diagnostic technique currently used for tissue metabolites assessing, but it also has great potential for visualizing the internal body structures. However, due to the low physiological level of phosphorus‐containing biomolecules, precise imaging requires the administration of an exogenous probe. Herein, this work describes the synthesis and MR characterization of a pioneering metal‐free 31P‐MR probe based on phosphorus‐containing polymeric zwitterion. The developed probe (pTMPC) is a well‐defined water‐soluble macromolecule characterized by a high content of naturally rare phosphorothioate groups providing a high‐intensity 31P‐MR signal clearly distinguishable from biological background both in vitro and in vitro. In addition, pTMPC can serve as a sensitive 31P‐MR sensor of pathological conditions in vivo because it undergoes oxidation‐induced structural changes in the presence of reactive oxygen species (ROS). Add to this the favorable 1H and 31P T1/T2 relaxation times and biocompatibility, pTMPC represents a conceptually new diagnostic, whose discovery opens up new possibilities in the field of 31P‐MR spectroscopy and imaging. Poly[O‐(2‐(methacryloyloxy)ethyl) O‐(2‐(trimethylamoniumyl) ethyl) phosphorothioate] (pTMPC) is a well‐defined polymeric zwitterion designed as a biocompatible probe for 31P‐MRI that provides a high intensity signal reliably distinguishable from the biological background in vivo. At the same time, pTMPC is prone to metabolic oxidation in the presence of reactive oxygen species, making it a prospective functional sensor of tumor tissue or inflammation.